Nanoparticles marvels: exploring the world of metallic nanoparticles - Chande, Sambhaji C; Tamboli, Firoj A (Journal of Postharvest Technology, 2024)
3.12.2023 16.01.2024 Based on a review of scientific research, the many kinds of organic nanoparticles that are metallic are  provided below. These nanoparticles are made of Ce, Ag, Au, Pt, Pd, Cu, Ni, Se, Fe, or its oxides. Metallic  nanoparticles are nanoscale metals that fall between one and one hundred nanometers in length, breadth,  and thickness. Faraday looked into the possibility of metallic nanoparticles in liquid form initially in 1857.  In 1908, Mie presented a quantitative interpretation regarding their color. There are contains a thorough  discussion of several characterization techniques, for example, X-ray diffraction, small-angle X-ray  scattering, ultraviolet (UV)-observable spectroscopy, Fourier-transform infrared spectrum analysis,  dynamic scattering of light, scanning electron microscopes, and transmission microscopy using electrons.  The metal nanoparticles are promising for use as weapons versus a range of hardy microorganisms. Their  capability to fight strains of bacteria and fungi resistant to antibiotics has been demonstrated by several  research. Metallic nanoparticles are used in organic chemistry as catalysis. When it comes to reducing  response time as well as increasing yields, this can result in noticeably better reaction performance. From  his review, the concept of Metallic nanoparticles, its advantages and disadvantages are described. It also  includes techniques for the synthesis of Metallic Nanoparticles and its applications..
Keywords: Nanosynthesis,; biological methods; gold; silver,; platinum nanoparticles